Kazakhstan Economy’s Current Development Stage: Issues and Solutions (Journal of Economic Research & Business Administration, 2016)
At present, the world economy is experiencing serious difficulties and it becomes a challenge for the countries, where the economic backbone is the oil production and export. Kazakhstan is already feeling the effects of the sharp drop in oil prices: GDP growth is reduced, causing problems with filling the state budget, also some disturbing trends in social indica tors were outlined in real terms. The second deep drop in oil prices over the past five years finally convinced us that Kazakhstan should actively re duce the technological gap with the developed countries, and this requires massive imports of advanced equipment and technology. In adjusting the development strategy, it is important to take into account the trap of the average level of development. In the creation of added value, services that are closely related to the knowledge economy play a crucial role. Innova tive economy can be created together and along with the development of human capital.
Keywords: public economy; oil prices; middle income country trap; knowledge economy; human capital.